Thermal Comfort Study of a Building Equipped with Nanofluid Assisted Thermoelectric Air Conditioner for the Hot Humid Climate of Malaysia - Balachandran, Mokhan (IRC, 2021)
This study explores the reliability and acceptability of thermal comfort by students in a building at University Teknologi Petronas fitted with a Nanofluid assisted Thermoelectric Air-conditioning (NTEAC) device in a tropical environment like Malaysia.